If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 5)(2 + 3i)(2 + -3i) = 0 Reorder the terms: (5 + x)(2 + 3i)(2 + -3i) = 0 Multiply (5 + x) * (2 + 3i) (5(2 + 3i) + x(2 + 3i))(2 + -3i) = 0 ((2 * 5 + 3i * 5) + x(2 + 3i))(2 + -3i) = 0 ((10 + 15i) + x(2 + 3i))(2 + -3i) = 0 (10 + 15i + (2 * x + 3i * x))(2 + -3i) = 0 Reorder the terms: (10 + 15i + (3ix + 2x))(2 + -3i) = 0 (10 + 15i + (3ix + 2x))(2 + -3i) = 0 (10 + 15i + 3ix + 2x)(2 + -3i) = 0 Multiply (10 + 15i + 3ix + 2x) * (2 + -3i) (10(2 + -3i) + 15i * (2 + -3i) + 3ix * (2 + -3i) + 2x * (2 + -3i)) = 0 ((2 * 10 + -3i * 10) + 15i * (2 + -3i) + 3ix * (2 + -3i) + 2x * (2 + -3i)) = 0 ((20 + -30i) + 15i * (2 + -3i) + 3ix * (2 + -3i) + 2x * (2 + -3i)) = 0 (20 + -30i + (2 * 15i + -3i * 15i) + 3ix * (2 + -3i) + 2x * (2 + -3i)) = 0 (20 + -30i + (30i + -45i2) + 3ix * (2 + -3i) + 2x * (2 + -3i)) = 0 (20 + -30i + 30i + -45i2 + (2 * 3ix + -3i * 3ix) + 2x * (2 + -3i)) = 0 (20 + -30i + 30i + -45i2 + (6ix + -9i2x) + 2x * (2 + -3i)) = 0 (20 + -30i + 30i + -45i2 + 6ix + -9i2x + (2 * 2x + -3i * 2x)) = 0 Reorder the terms: (20 + -30i + 30i + -45i2 + 6ix + -9i2x + (-6ix + 4x)) = 0 (20 + -30i + 30i + -45i2 + 6ix + -9i2x + (-6ix + 4x)) = 0 Reorder the terms: (20 + -30i + 30i + 6ix + -6ix + -45i2 + -9i2x + 4x) = 0 Combine like terms: -30i + 30i = 0 (20 + 0 + 6ix + -6ix + -45i2 + -9i2x + 4x) = 0 (20 + 6ix + -6ix + -45i2 + -9i2x + 4x) = 0 Combine like terms: 6ix + -6ix = 0 (20 + 0 + -45i2 + -9i2x + 4x) = 0 (20 + -45i2 + -9i2x + 4x) = 0 Solving 20 + -45i2 + -9i2x + 4x = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -45i2 + -9i2x + -20 + 4x = 0 + -20 Reorder the terms: 20 + -20 + -45i2 + -9i2x + 4x = 0 + -20 Combine like terms: 20 + -20 = 0 0 + -45i2 + -9i2x + 4x = 0 + -20 -45i2 + -9i2x + 4x = 0 + -20 Combine like terms: 0 + -20 = -20 -45i2 + -9i2x + 4x = -20 Add '-4x' to each side of the equation. -45i2 + -9i2x + 4x + -4x = -20 + -4x Combine like terms: 4x + -4x = 0 -45i2 + -9i2x + 0 = -20 + -4x -45i2 + -9i2x = -20 + -4x Reorder the terms: 20 + -45i2 + -9i2x + 4x = -20 + -4x + 20 + 4x Reorder the terms: 20 + -45i2 + -9i2x + 4x = -20 + 20 + -4x + 4x Combine like terms: -20 + 20 = 0 20 + -45i2 + -9i2x + 4x = 0 + -4x + 4x 20 + -45i2 + -9i2x + 4x = -4x + 4x Combine like terms: -4x + 4x = 0 20 + -45i2 + -9i2x + 4x = 0 The solution to this equation could not be determined.
| 2a-3b=8 | | 0=X^2-10X-39 | | 6x^6+7x^4+8x-2-7x^6-3x^3-7= | | 22x-6=20 | | 2xm+9x-3m-21=0 | | 7-4+7x=38 | | (x+5)(2+3i)=0 | | 19x+2y=50 | | 37b+7=8.1b-19.4 | | 4x+7-8x-12=16 | | 7(x-2)+5y=10 | | X-19=-42 | | x+(x-3)=4 | | 2-x=2x+1 | | 4x^2+9y^2-32x-36y+64=0 | | 18-3y=4x | | -9r-4=4r+35 | | 3[4-(y+2)]= | | 9x+4-x=2(3x+6) | | -4(-5x+1)=176 | | p*13=4 | | h=5t^2+30t+35 | | 4x-(x-2)=11 | | 2h+5=3h-15 | | 16(9)=8x | | 0.5xy(-2x^2y^3)= | | 2(-1+1x)=-10 | | (7+x)7=(6+15)6 | | 0=(-16t^2)+8t+12 | | (27+x)27=(45)45 | | X+3+5=8+2x | | (10+x)10=(11+9)9 |